Plasma debinding and pre-sintering of injected parts - Santos Maria Antônia dos; Neivock Matheus Piazzalunga; Maliska Ana Maria; Klein Aloísio Nelmo; Muzart Joel Louis Rene (Materials Research, 2004)
Results of polypropylene removal in injected metallic parts by using plasma technology are presented. The samples were injected with 55.18% Vol. of unalloyed iron powder, 23.57% Vol. of paraffin and 21.25% Vol. of polypropylene. The paraffin was previously removed in hexane bath, followed by a treatment in abnormal glow discharge of argon and hydrogen for the removal of the polypropylene. The electric discharge was generated in two configurations: a confined anode-cathode with the samples placed on the anode and a confined grid (anode)-cathode system with the sample placed on a holder at floating potential inside the grid. In the first geometry, electrons bombarded the sample surface, while in the second, they are collected by the grid. The samples were characterized by mass loss measurements and scanning electron microscopy. The results showed that the hydrogen discharge was more efficient for both configurations, which is attributed to the high reactivity of hydrogen atoms produced in the discharge. In addition, when plasma debinding was performed at 400 ºC for 10 min, by using the confined anode-cathode configuration, the polypropylene removal was total, while in the confined grid (anode)-cathode geometry the removal was approximately 32%. The higher polypropylene removing observed in the anode-cathode configuration is attributed to electron bombardment of the surface of the sample.